Cystocele management in multisurgical patients: a comprehensive case report emphasizing advanced diagnostic and surgical precision - Bhimgade, Prajakta; Tholu, Chandana P.; Dange, Shalini; Choudhary, Amruta A.; Yadav, Anita; Mundle, Shuchita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Pelvic organ prolapses (POP), particularly cystocele, presents significant challenges in postmenopausal women, exacerbated in those with multiple caesarean sections (LSCS) and comorbidities like diabetes mellitus. This case report details the successful management of a 62-year-old woman with a large cystocele, three LSCS, and diabetes mellitus. Thorough preoperative evaluation, including ultrasound and diagnostic laparoscopy, guided surgical planning. Anterior colporrhaphy restored support to the anterior vaginal wall. Perioperative care included strict glycemic control and antibiotic prophylaxis. Multidisciplinary collaboration ensured comprehensive management. This case highlights the importance of advanced diagnostics, meticulous surgical planning, and multidisciplinary care in complex cystocele cases.